Design, assembly and experimental tests of a Savonius type wind turbine - Salazar Marin, Edgar Alonso; Rodríguez, Andrés Felipe (Scientia et Technica, 2019)
The present research project focuses on the development of a Savonius type wind turbine, where a literature review is initially carried out to recognize the appropriate parameters for its design such as turbulence, wind velocity, and air density, followed by a design methodology to achieve the dimensioning by means of resistance calculation and selection of component materials, after having the final concept defined. Using computational tools such as Solidworks, Inventor, Simulation Mechanical, the design stage was validated through simulation to study the dynamic fluid behavior and the components were modeled to evaluate their response to wind loads, verifying their resistance. Subsequently, according to the modeling, the detailed drawings of the components of the turbine were obtained, with which they were assembled. Finally, having the physical model of the Savonius wind turbine, experimental tests were carried out in the laboratory of Fluids and Hydraulic Machines of the Technological University of Pereira.